The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1007/s11082-022-03515-z
|View full text |Cite
|
Sign up to set email alerts
|

Bi-doped SnO2 transparent conducting thin films deposited by spray pyrolysis: structural, electrical, optical, and photo-thermoelectric properties

Abstract: In this research, light and heavy Bi-doped SnO 2 thin lms were prepared on glass substrates by spray pyrolysis technique. The effect of heavy doped-Bi on the structural, morphological, electrical, photothermo-electrical, optical properties of SnO 2 lms has been investigated.The Bi/Sn atomic ratios (x = [Bi/Sn]) were varied from 0 to 0.30 in the spray solution.X-ray diffraction analysis showed the formation of SnO 2 tetragonal rutile structure in low doped deposited lms and amorphous structure for heavy Bi-dope… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 40 publications
1
0
0
Order By: Relevance
“…Yakuphanoglu [11] observed an S value of −500 µV/K a 300 K for a SnO2 thin film coated on an ITO substrate by dip coating, and Trejo-Zamudio et al [31] reported that the maximum S value found was −200 µV/K at 300 K for a SnO thin film Bi-doped by spray pyrolysis, which is consistent with our measurements. In ad dition to this, several previously documented studies on SnO2 and dissimilar metal-doped SnO2 thin films [32][33][34] consistently align with our work in terms of their corresponding Seebeck coefficients. In Figure 5, we present a comparison of data from the reported stud ies on oxide thin films.…”
Section: Thermoelectric Propertiessupporting
confidence: 91%
“…Yakuphanoglu [11] observed an S value of −500 µV/K a 300 K for a SnO2 thin film coated on an ITO substrate by dip coating, and Trejo-Zamudio et al [31] reported that the maximum S value found was −200 µV/K at 300 K for a SnO thin film Bi-doped by spray pyrolysis, which is consistent with our measurements. In ad dition to this, several previously documented studies on SnO2 and dissimilar metal-doped SnO2 thin films [32][33][34] consistently align with our work in terms of their corresponding Seebeck coefficients. In Figure 5, we present a comparison of data from the reported stud ies on oxide thin films.…”
Section: Thermoelectric Propertiessupporting
confidence: 91%